Digital audio watermarking techniques and technologies applications and benchmarks - Cvejic, Nedeljko; Seppanen, Tapio (Gale virtual reference library, 2008)
Presents digital audio watermarking as a new and alternative method to enforce intellectual property rights and protect digital audio from tampering. Provides theoretical frameworks, recent research findings, and practical applications.